2005
DOI: 10.1645/ge-3357rm
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Paragonimus heterotremus Eggs in Experimentally Infected Cats by a Polymerase Chain Reaction–Based Method

Abstract: A polymerase chain reaction (PCR) procedure for the detection of Paragonimus heterotremus eggs in stool samples was developed and compared with Stoll's egg count method. The primers were designed on the basis of a previously constructed pPH-13-specific DNA probe, which produced an approximate 0.5-kb amplified product. This PCR method could detect as few as 5 eggs in 0.6 g of artificially inoculated feces of a healthy control cat or as little as 1 x 10(-4) ng of P. heterotremus genomic DNA. The assay had 100% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…[24][25][26] However, relatively few studies have attempted to detect Paragonimus DNA in the definitive host. [27][28][29] Our PCR studies confirmed the presence of P. kellicotti DNA in clinical specimens from two Missouri cases. Both patients had clinically compatible illnesses after ingestion of raw crayfish.…”
Section: Discussionsupporting
confidence: 66%
“…[24][25][26] However, relatively few studies have attempted to detect Paragonimus DNA in the definitive host. [27][28][29] Our PCR studies confirmed the presence of P. kellicotti DNA in clinical specimens from two Missouri cases. Both patients had clinically compatible illnesses after ingestion of raw crayfish.…”
Section: Discussionsupporting
confidence: 66%
“…This approach should be evaluated further using more faecal samples and highly specific and sensitive primers (Intapan et al, 2005). Serology, the copro-DNA test and detection of eggs in sputum (or faeces) are essential for differentiation of paragonimiasis from other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular assays, using PCR, have been developed for Opisthorchis viverrini (Wongratanacheewin et al 2002), Paragonimus spp. (Intapan et al 2005) and C. sinensis (Parvathi et al 2007) that offer improved sensitivity. Advances in recombinant protein expression are facilitating the development of ELISA-based detection methods.…”
Section: Zoonotic Trematode Infections (A) Fasciolosismentioning
confidence: 99%